Electric field modulated photoluminescence in ferroelectric ceramics for photosensitive device applications. (August 2022) - Borkar, Hitesh; Mishra, Siju; Gangwar, Jitendra; Haranath, D.; Kumar, Ashok
Highlights: The degree of freedom is controlled by electronic excitations in ferroelectrics. Elimination of chemical convention method and tuning of photoluminescence were achieved. Design of electrically controlled advanced light switching devices could be made possible. Abstract: The degree of freedom controlled by electronic excitations in ferroelectrics provides innovative opportunities for information processing and optoelectronics. In the current work, electrically modulated photoluminescence (PL) has been demonstrated in Pb1-x (Li0.5 Bi0.5 )x (Zr1-y Tiy )O3 (PLBZT) for x =  0.3–0.5 and y=0.80, respectively. The primary approach was made directly to modulate the PL property by applying an external electric field in an in-situ way. However, the modulation of PL is possible in perovskite oxides when the distortion of structural symmetry arose under external electrical bias in particularly ferroelectrics, implying reversible and dynamic tuning of PL emission. Hence, there is emergence of new channels where radiative and/or forbidden transitions arise from the positional disorder of the system under the application of an external electric field. These studies establish the realization of tunable PL ferroelectric ceramics with high repeatability, flexibility, and faster response towards designing advanced light switching devices. Graphical abstract: Image, graphical abstract